Ten-year comparison of pericardial tissue valves versus mechanical prostheses for aortic valve replacement in patients younger than 60 years of age - Weber, Alberto; Noureddine, Hassan; Englberger, Lars; Dick, Florian; Gahl, Brigitta; Aymard, Thierry; Czerny, Martin; Tevaearai, Hendrik; Stalder, Mario; Carrel, Thierry Pierre (The Journal of thoracic and cardiovascular surgery, 2012)
Aortic valve replacement using a tissue valve is controversial for patients younger than 60 years old. The long-term survival in this age group, the expected event rates during long-term follow-up, and valve-related complications are not clearly determined. From January 2000 to December 2009, overall survival, valve-related events, and echocardiographic outcomes were analyzed in all patients younger than 60 years of age, who underwent biologic aortic valve replacement. Patients who received a Perimount Carpentier-Edwards pericardial tissue valve (n = 103) were selected and compared with a propensity matched group of 103 patients who received aortic valve replacement using a mechanical bileaflet valve. The mean follow-up was 33 ± 24 months (range, 2-120), and the mean age at implantation was 50.6 ± 8.8 years (bioprosthesis, 55 ± 8.9 years; mechanical valve, 50 ± 8.6 years; P = .03). Survival was significantly reduced in patients after biologic aortic valve replacement (90.3% vs 98%; P = .038). Freedom from all valve-related complications (bioprosthesis, 54.5%; mechanical valve, 51.6%; P = NS) and freedom from reoperation (bioprostheses, 100%; mechanical valve, 98%; P = NS) were comparable in both groups. The average transvalvular mean (11.2 ± 4.2 mm Hg vs 10.5 ± 6.0 mm Hg, P = .05) and peak (19.9 ± 6.7 mm Hg vs 16.7 ± 8.0 mm Hg, P = .03) gradients were greater after biologic aortic valve replacement. Regression of the left ventricular mass index was more pronounced after mechanical valve replacement (118.5 ± 24.9 g/m(2) vs 126.5 ± 38.5 g/m(2); P = NS). The echocardiographic patient-prosthesis mismatch was greater at follow-up after biological aortic valve replacement (0.876 ± 0.2 cm(2)/m(2) vs 1.11 ± 0.4 cm(2)/m(2); P = .01). Oral anticoagulation was a protective factor for survival among the bioprosthetic valve patients (P = .024). In the present limited cohort of patients younger than 60 years old, biologic aortic valve replacement was associated with reduced mid-term survival compared with survival after mechanical aortic valve replacement. Despite similar valve-related event rates in both groups, the better hemodynamic performance of the mechanical valves and/or protective effect of oral anticoagulation seemed to improve the outcome. The transcatheter valve-in-valve intervention as potential treatment of tissue valve degeneration should not be considered the sole bailout strategy for younger patients because no evidence is available that this would improve the outcome.